Symptom Clusters and Quality of Life among Women Living with Cancer - Pahria, Tuti; Yuliana, Yuliana; Praptiwi, Atlastieka; Atout, Maha; Agustina, Hana Rizmadewi (Jurnal Keperawatan Soedirman, 2023)
The prevalence of cancer in Indonesia has increased and is one of the biggest causes of death. Symptom clusters, a collection of symptoms in cancer patients that appear together and are related to one another, can affect the quality of life of cancer patients. This study aims to identify the relationship between symptom clusters and the quality of life of advanced cancer patients. This research used cross-sectional quantitative survey data from a cancer patient care unit at a referral hospital in West Java Province with a total of 140 respondents. Consecutive sampling was conducted for three months in stage III or IV cancer patients who were undergoing therapy. This study used descriptive analysis, factor analysis with the Principal Components Analysis (PCA) approach, and multiple linear regression analysis. Five symptom clusters were identified: the psychological cluster, the gastrointestinal cluster, the numbness cluster, the pain cluster, and the respiratory distress cluster. The results showed that symptom clusters influence the quality-of-life dimension. The symptom clusters’ coefficient of determination (R2) for the physical dimension was 0.231 (weak), the role dimension was 0.191 (very weak), the emotional dimension was 0.484 (moderate), the cognitive dimension was 0.011 (very weak), the social dimension was 0.420 (moderate), and the general-health dimension was 0.202 (weak).